The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1097/00001756-199803300-00001
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate uptake is decreased tardively in the spinal cord of FALS mice

Abstract: This study examined high affinity Na+-dependent uptake of glutamate in synaptosomal preparations from spinal cord in mice that express a dominant mutation of human copper/zinc superoxide dismutase (SOD1) and represent an animal model of amyotrophic lateral sclerosis (ALS). Their muscle strength was also monitored by a grip traction test throughout their lifespan. The high affinity Na+-dependent uptake of [3H]glutamate was decreased between 120 and 150 days of age. A marked and significant decrease in Vmax (-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 8 publications
6
34
0
Order By: Relevance
“…We also evaluated rotarod performance during the same time period and found that the performance rate was reduced from ~71 days of age, although it was not consistently significantly different until 113 days of age (due in part to the use of non-parametric tests and our conservative definition of a consistent significant difference). Our findings are in agreement with those of Canton et al (1998; and Weydt et al (2003), which also demonstrated the presence of chronic limb muscle weakness. Interestingly, we found that SOD1-G93A and control mice exhibited similar levels of locomotor activity, even at end-stage, despite early deficits in grip strength and rotarod performance.…”
Section: Fore-and Hindlimb Motor Deficitssupporting
confidence: 92%
See 1 more Smart Citation
“…We also evaluated rotarod performance during the same time period and found that the performance rate was reduced from ~71 days of age, although it was not consistently significantly different until 113 days of age (due in part to the use of non-parametric tests and our conservative definition of a consistent significant difference). Our findings are in agreement with those of Canton et al (1998; and Weydt et al (2003), which also demonstrated the presence of chronic limb muscle weakness. Interestingly, we found that SOD1-G93A and control mice exhibited similar levels of locomotor activity, even at end-stage, despite early deficits in grip strength and rotarod performance.…”
Section: Fore-and Hindlimb Motor Deficitssupporting
confidence: 92%
“…In contrast, other studies revealed long-standing deficits apparent at earlier time-points. Using a grip strength meter, Canton et al (1998) demonstrated reduced combined limb grip strength in SOD1-G93A mice compared to controls from approximately 35 days of age. Another study by Canton et al (2001) demonstrated significantly reduced combined limb grip strength in SOD1-G93A mice compared to controls from 55 days of age.…”
Section: Fore-and Hindlimb Motor Deficitsmentioning
confidence: 98%
“…In mutant SOD1 mice, several studies have shown decreased EAAT2 protein and downregulation of glutamate-transport activity in affected CNS areas (9,15,20,23,41,151,153,155). Similar results are found in the SOD1-G93A and H46R transgenic rats (41, 68) (see also Fig.…”
Section: Astroglia Dysfunction In Als Occurs Through Different Synergsupporting
confidence: 74%
“…Several studies in the mouse model of ALS showed that changes in the EAAT2 expression levels and glutamateuptake activity are found only in the ventral horn of the affected spinal cord at a late stage of disease (9,23,41). An .…”
Section: Astroglia Dysfunction In Als Occurs Through Different Synergmentioning
confidence: 99%
“…This may weaken the tolerance of motoneurons to glutamate. Second, mutant SOD1 is also capable of impairing the function of glial glutamate transporter GLT-1 (Canton et al 1998;Pedersen et al 1998;Trotti et al 1999). Particularly striking is the recent finding that transgenic rats expressing mutant SOD1 G93A have a dramatic decrease in GLT-1 in the ventral horn of their spinal cords (Howland et al 2002).…”
Section: Discussionmentioning
confidence: 99%